Identifying Occupational Stress and Coping Strategies - Palaniappan, Kavitha (IntechOpen, 2023)
Occupational stress is a global phenomenon and this book aims to identify the various factors associated with occupational stress in industrial and healthcare workers while also suggesting some potential coping strategies that have been found to help in overcoming such occupational stress. After reading this book, I trust that readers will be able to appreciate the importance of coping strategies for mental wellbeing in the workplace.